2023
DOI: 10.3390/brainsci14010006
|View full text |Cite
|
Sign up to set email alerts
|

Global Neuropsychopharmacological Prescription Trends in Adults with Schizophrenia, Clinical Correlates and Implications for Practice: A Scoping Review

Jiangbo Ying,
Qian Hui Chew,
Yuxi Wang
et al.

Abstract: It is important to examine the psychotropic prescription practices in schizophrenia, as it can inform regarding changing treatment choices and related patient profiles. No recent reviews have evaluated the global neuropsychopharmacological prescription patterns in adults with schizophrenia. A systematic search of the literature published from 2002 to 2023 found 88 empirical papers pertinent to the utilization of psychotropic agents. Globally, there were wide inter-country and inter-regional variations in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…Additionally, across all dose levels, antidepressant exposure is linked to a reduction in CVD mortality in this geriatric population. Combining antipsychotics with antidepressants is a frequently used clinical approach to address symptoms in individuals with schizophrenia [ 19 ]. Tiihonen et al found a decline in all-cause mortality among schizophrenia patients receiving antidepressant treatment compared to those without exposure to antidepressants, aligning with our own findings [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, across all dose levels, antidepressant exposure is linked to a reduction in CVD mortality in this geriatric population. Combining antipsychotics with antidepressants is a frequently used clinical approach to address symptoms in individuals with schizophrenia [ 19 ]. Tiihonen et al found a decline in all-cause mortality among schizophrenia patients receiving antidepressant treatment compared to those without exposure to antidepressants, aligning with our own findings [ 12 ].…”
Section: Discussionmentioning
confidence: 99%